Spatial analysis of reposition costs of soil nutrients in a hydrographic basin - da Cunha e Silva, Darllan Collins [UNESP]; Sales, Jomil Costa Abreu; Simonetti, Vanessa Cezar [UNESP]; Lourenço, Roberto Wagner [UNESP] (Centro Universitario de Maringa, 2020)
So that one may obtain the economic value of an environmental resource, its monetary value should be estimated in relation to other goods/services available in the economy. Environmental valorization methods currently used are relatively new and the variables in the process may not be known or partially known. One method is the Reposition Cost that calculates the value of reparation from a damage. Current paper applied the reposition cost method in the economic valorization of nutrient loss by soil erosion in the hydrographic basin of the river Una, Brazil, through geoprocessing to evaluate spatially the area under analysis. Thirty-five samples were collected and the soil´s nutrients quantified, Ca, Mg, P and K. Concentrations were spatialized and annual loss estimated, with reposition costs. In more than 89% of the studied area, the reposition cost of K, P, Ca and Mg of the three fertilizers employed (potassium chloride, potassium chlorate, simple superphosphate and lime) reached about R$ 0.01 per m2. Total reposition cost was R$ 352,846.43. The spatialization of reposition costs showed which areas required special attention of the government with regard to monitoring and proposition of sustainability.
Análise espacial do custo de reposição de nutrientes do solo em uma bacia hidrográfica
Keywords: Fertilizers; Geo-processing; Geo-spacing; Geo-statistics; Soil